2011
DOI: 10.1089/neu.2010.1581
|View full text |Cite
|
Sign up to set email alerts
|

Phenylephrine Infusion Prevents Impairment of ATP- and Calcium-Sensitive Potassium Channel-Mediated Cerebrovasodilation after Brain Injury in Female, but Aggravates Impairment in Male, Piglets through Modulation of ERK MAPK Upregulation

Abstract: Traumatic brain injury (TBI) contributes to morbidity in children and boys, and hypotension worsens outcome. Extracellular signal-related kinase (ERK) mitogen-activated protein kinase (MAPK) is upregulated more in males and reduces cerebral blood flow (CBF) after fluid percussion injury (FPI). Increased cerebral perfusion pressure (CPP) via phenylephrine (Phe) sex-dependently improves impairment of the cerebral autoregulation seen after FPI through modulation of ERK MAPK upregulation, which is aggravated in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 27 publications
2
23
1
Order By: Relevance
“…We also showed that the ET-1 antagonist BQ 123 blunted while the free radical scavenger SODCAT blocked ERK MAPK release after FPI, supportive of the sequential pathway wherein FPI releases ET-1 to increase superoxide which in turn releases ERK MAPK to impair K channel mediated cerebrovasodilation and thereby cerebral autoregulation (Armstead and Vavilala 2013). More ET-1, activated oxygen, and ERK MAPK are released in males compared to females to sequentially impair K channel mediated cerebrovasodilation, contributing to greater impairment of autoregulation after TBI (Armstead 2000; Armstead et al 2011; Armstead and Vavilala 2013). New data in the present study show that DA equivalently blocks upregulation of ERK MAPK in male and female newborn and juvenile pigs.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that the ET-1 antagonist BQ 123 blunted while the free radical scavenger SODCAT blocked ERK MAPK release after FPI, supportive of the sequential pathway wherein FPI releases ET-1 to increase superoxide which in turn releases ERK MAPK to impair K channel mediated cerebrovasodilation and thereby cerebral autoregulation (Armstead and Vavilala 2013). More ET-1, activated oxygen, and ERK MAPK are released in males compared to females to sequentially impair K channel mediated cerebrovasodilation, contributing to greater impairment of autoregulation after TBI (Armstead 2000; Armstead et al 2011; Armstead and Vavilala 2013). New data in the present study show that DA equivalently blocks upregulation of ERK MAPK in male and female newborn and juvenile pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Phe augments impairment of autoregulation in males after TBI both because it promotes release of a spasmogen and subsequent block of Katp and Kca channels as well because it simultaneously limits release of an endogenous neuroprotectant (Fig 1). 66 In contrast, DA completely blocked ET-1 and ERK MAPK upregulation in both newborn male and female piglets after FPI (Fig 1), 61 serving as an explanation for equivalent protection of autoregulation post injury in male and female piglets.…”
Section: Pathophysiology Of Cerebral Autoregulation In Tbi: Outcome Amentioning
confidence: 91%
“…These covariates were selected due to their potential influence on cerebral autoregulation and neurologic injury. [68, 2325] Relationships between perinatal insult score and brain injury were estimated with polytomous regression for ordered categorical outcomes. Finally, we examined the neonates’ blood pressures in relation to MAP OPT as they progressed through hypothermia, rewarming, and normothermia using a Pearson’s correlation coefficient to compare the percentages of the autoregulation monitoring period with blood pressure below, within, or above MAP OPT between hypothermia vs. rewarming; hypothermia vs. normothermia; and rewarming vs. normothermia.…”
Section: Methodsmentioning
confidence: 99%
“…However, these studies were too small to control for confounders that affect autoregulation, such as the arterial partial pressure of carbon dioxide (PaCO 2 ) [6] and vasopressors. [7, 8] Here, we studied a larger cohort to evaluate autoregulation independent of PaCO 2 , vasopressors, perinatal insult severity, and seizures.…”
Section: Introductionmentioning
confidence: 99%